Beyond Abolition: Challenging the “un-visibility” of enslavement-associated commerce in England and New England - Campbell, Sophie Helen (2022)
This research analyses 48 heritage sites in England and New England, which offered narratives of transatlantic slavery in 2018–2019. Building on previous critiques of public memory of slavery, I focus on highlighting the economic connections of what I term enslavement-associated commerce (EAC). Researching sites in England and New England enabled a transnational comparison between two regions that both profited from enslavement, but largely at a geographic distance. I argue that changing our focus of vision from sites of enslavement to sites of EAC reveals the widespread spectral traces, impact, and importance of slavery to both England and New England. In both regions the analysed sites of intervention participate in the act of challenging the “un-visibility” of EAC, which was buried beneath abolition, as part of what I call the defenders of liberty heritage narrative (DOLHN). Conscious of this context, this thesis draws on decades of historical literature to undertake in-depth analysis of the scope of narratives offered, across the 48 case studies. These include museums, memorials, historic houses and cotton mills. I investigate whether the interventions within these sites effectively acknowledge the impact of EAC, and consequently its relevance to the heritage narratives of England and New England. While collectively they do reveal the importance of EAC, there are recurring limitations in the narratives, including a predominant focus on individual wealthy enslavers and ports. Moving forward, I encourage the development of more complex narratives of EAC, which better recognise the contribution of enslaved labourers to modern capitalism.